2012
DOI: 10.1007/978-3-642-27660-6_19
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Model Checking for Modal Dependence Logic

Abstract: Modal dependence logic (MDL) was introduced recently by Väänänen. It enhances the basic modal language by an operator =(·). For propositional variables p 1 , . . . , p n the atomic formula =(p 1 , . . . , p n−1 , p n ) intuitively states that the value of p n is determined solely by those of p 1 , . . . , p n−1 .We show that model checking for MDL formulae over Kripke structures is NPcomplete and further consider fragments of MDL obtained by restricting the set of allowed propositional and modal connectives. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…In (Grädel, ), it was also shown that, for the fragment of scriptD with constancy atoms only, the model checking problem is PSPACE‐complete. For modal versions of dependence logic, the model checking problem has been studied in (Ebbing and Lohmann, ) and (Ebbing et al, ), and the satisfiability problem in (Lohmann and Vollmer, ) and (Sevenster, ).…”
Section: Complexity Results For Dependence Logicmentioning
confidence: 99%
See 2 more Smart Citations
“…In (Grädel, ), it was also shown that, for the fragment of scriptD with constancy atoms only, the model checking problem is PSPACE‐complete. For modal versions of dependence logic, the model checking problem has been studied in (Ebbing and Lohmann, ) and (Ebbing et al, ), and the satisfiability problem in (Lohmann and Vollmer, ) and (Sevenster, ).…”
Section: Complexity Results For Dependence Logicmentioning
confidence: 99%
“…The semantics of MDL is defined with respect to sets of worlds in a frame (Kripke structure). Modal dependence logic has been further studied in (Sevenster, ; Lohmann, ; Ebbing and Lohmann, ), and (Lohmann and Vollmer, ). Also, the extension of MDL by the intuitionistic implication has been studied in (Ebbing et al, ). Extensions of dependence logic by generalized quantifiers have been defined and studied in (Engström, ; Engström and Kontinen, ), and (Durand et al, ). A dynamic version of dependence logic was introduced in (Galliani, ) and (Galliani, ) in which formulas are interpreted as transitions between information states.…”
Section: Some Variants and Extensions Of Dependence Logicmentioning
confidence: 99%
See 1 more Smart Citation
“…From a computational complexity perspective, DL is well understood: most of the possible operator fragments have been classified [16,17]. However, it turned out that model checking and satisfiability for propositional dependence logic PDL are already NP-complete [10,24]. As a result, tractable enumeration of solutions in the full logic is impossible (unless P and NP coincide) and we focus on a fragment of PDL which we will call, for historical reasons, the Poor Man's fragment [18].…”
Section: Introductionmentioning
confidence: 99%
“…In [12], Lohmann and Vollmer proved complexity results for syntactic fragments of MDL. Ebbing and Lohmann [4] showed that the model checking problem for MDL is NP-complete. Also, in recent years research on complexity questions has been active; see e.g.…”
Section: Introductionmentioning
confidence: 99%